The South China Sea Disputes: The Energy Dimensions - Umbach, Frank (2017)
The regional oil and gas reserves in the South China Sea have become economically and geopolitically less important due to oversupply in the global oil and gas markets, new diversification options and low oil and gas prices. Beijing’s deepwater projects in the South China Sea are not exclusively or primarily driven by commercial factors.